Synthesis, spectral studies and antimicrobial evaluation of 6,6--(1,2-benzenediazo) bis (3-amino benzoic acid) complexes with some metal ions - Amer J.Jarad, et.al; NibrasAbdul-Ameer Aboud*, Suhad Shakir,Dhafir T. Ajeel Al-Heetim (Al-Qadisiyah Journal of Pure Science, 2017)
The Ligand 6,6--(1,2-benzenediazo) bis (3-aminobenzoicacid) derived from o-phenylenediamine and 3-aminobenzoicacid was synthesized. The prepared ligand was identified by Microelemental Analysis, 1HNMR, FT-IR and UV-Vis spectroscopic techniques. Treatment of the ligand with the following metal ions (CoII, NiII, CuII and ZnII ) in aqueous ethanol with a 1:1 M:L ratio and at optimum pH. Characterization of these compounds has been done on the basis of elemental analysis, electronic data, FT-IR and UV-Vis, as well as magnetic susceptibility and conductivity measurements. The nature of the complexes formed were studied following the mole ratio and continuous variation methods, Beer's law obeyed over a concentration range (1Ã—10-4 - 3Ã—10-4 M). High molar absorbtivity of the complex solutions were observed. On the basis of physicochemical data tetrahedral geometries were assigned for the complexes. The ligand and metal complexes were screened for their antimicrobial activity.